EFFECT OF TURMERIC EXTRACT ON BLOOD PARAMETERS, FEED EFFICIENCY AND ABDOMINAL FAT CONTENT IN BROILERS - Sugiharto, S.; Isroli, I.; Widiastuti, E.; Prabowo, N.S. (Diponegoro University, 2011)
The experiment was carried out to investigate the effect of turmeric extract on blood parameters,feed efficiency and abdominal fat content in broilers. A total of 100 mixed-sexes Lohman chicks wereused in the experiment set up with completely randomized design of 5 different doses of turmeric extractgiven orally start from day-15 to day-35. The chicks given no turmeric extract were used as a control(T0), whereas T1, T2, T3 and T4 were the chicks given turmeric extract of 200, 400, 600 and 800mg/kg-live BW, respectively. Hemoglobin values of broilers given turmeric extract 800 mg/kg-live BWwas significantly higher (p<0.05) at week-3 and week-4, but not at week-5, compared to broilers giventurmeric extract with lower doses or control group. Turmeric extract did not affect significantly (p>0.05)the concentration of erythrocytes, the levels of hematocrit as well as FCR and abdominal fat content ofbroiler. Turmeric extract seemed to be able to improve the digestion and metabolism (of fat) resulted inenhanced production of hemoglobin in broilers. The hypolipidemic effect of turmeric that could hamperits potential to promote the growth of broilers per se might explain why turmeric could not improve thefeed efficiency of broiler.